Publisher Correction: Clonal evolution of acute myeloid leukemia revealed by high-throughput single-cell genomics - Kiyomi Morita; Feng Wang; Katharina Jahn; Tianyuan Hu; Tomoyuki Tanaka; Yuya Sasaki; Jack Kuipers; Sanam Loghavi; Sa A. Wang; Yuanqing Yan; Ken Furudate; Jairo Matthews; et al. (Nature Communications, 2020)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-020-19902-7